2018
DOI: 10.1111/tid.12904
|View full text |Cite
|
Sign up to set email alerts
|

A 20‐year experience with nocardiosis in solid organ transplant (SOT) recipients in the Southwestern United States: A single‐center study

Abstract: Based on our findings, daily 1 DS TMP/SMX prophylaxis did not appear to provide reliable protection against nocardiosis. However, we could not state definitely that TMP/SMX prophylaxis was or wasn't protective because of lack control group. None of the Fisher's exact tests revealed associations between the tested risk factors and either disease dissemination or mortality. This could be due to a true lack of association between the variables in each pair. However, it is also likely that our relatively small sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 21 publications
2
35
2
Order By: Relevance
“…Of note, amikacin was the only tested drug with proven in vitro efficacy against all Nocardia abscessus isolates in this cohort. The study findings add to the available data on susceptibility testing and demonstrate increasing resistance to commonly recommended antibiotics (Minero et al, 2009;Uhde et al, 2010;Lebeaux et al, 2018;Schlaberg et al, 2014;Valdezate et al, 2017;McTaggart et al, 2015). In addition, the data are in line with those of a recent study from France, showing that N. farcinica is the most common species in human infection in Western Europe, with a distinct pattern of susceptibility (Lebeaux et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…Of note, amikacin was the only tested drug with proven in vitro efficacy against all Nocardia abscessus isolates in this cohort. The study findings add to the available data on susceptibility testing and demonstrate increasing resistance to commonly recommended antibiotics (Minero et al, 2009;Uhde et al, 2010;Lebeaux et al, 2018;Schlaberg et al, 2014;Valdezate et al, 2017;McTaggart et al, 2015). In addition, the data are in line with those of a recent study from France, showing that N. farcinica is the most common species in human infection in Western Europe, with a distinct pattern of susceptibility (Lebeaux et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…Hence, due to the possibility of a resistant species (mainly N farcinica ), the benefits of synergistic therapy, and the high mortality that may be associated with nocardiosis, it might be beneficial to use a combination of agents as initial therapy in patients who are seriously ill and/or have disseminated or CNS disease . With regards to prophylaxis, TMP‐SMX for PJP in SOT recipients has not been consistently shown to prevent breakthrough nocardiosis, presumably due to its usage only 2‐3 times per week unlike daily . Our patient was on prophylaxis since the transplant and yet acquired the disease.…”
Section: Discussionmentioning
confidence: 96%
“…Among SOT recipients, the incidence of nocardiosis ranges from 0.04% to 3.5%, with the highest frequency in recipients of lung (3.5%), followed by recipients of heart (2.5%), intestine (1.3%), kidney (0.2%), and liver (0.1%) transplants . As per a retrospective European study, nocardiosis occurred at a median of 17.5 (range, 2‐244) months after transplant .…”
Section: Discussionmentioning
confidence: 97%
“…A recent large-scale study of 54 cases of nocardiosis in solid organ transplant patients found a similar proportion of heart transplant recipients among the cases (37%). 6 …”
Section: Discussionmentioning
confidence: 99%